Magnetic Resonance Imaging–Generated Synthetic Computed Tomography in Pediatric Spine Patients - George E. Michael, BS; Suhas K Etigunta, BS; Andy Liu, BS; Meliza Perales, RN/BSN; Cristabelle Alexander, MS; Christopher Watterson, MD; Daniel Hoghoughi, MRSO; Norman Gellada, BSHS; David L Skaggs, MD, MMM; Kenneth D Illingworth, MD (JBJS Open Access)
Background:. Computed tomography (CT) and magnetic resonance imaging are common imaging studies used to evaluate pediatric spine patients. Novel MRI-generated synthetic CT (sCT) images have demonstrated near equivalence in accuracy when compared with traditional CT (tCT) in cadaveric studies. This recent advancement allows potential visualization of both bony and soft tissue anatomy without harmful ionizing radiation. To date, no literature reports the use of sCT in the evaluation of pediatric spinal pathologies. This study aimed to evaluate the clinical utility of sCT in managing pediatric and adolescent patients with various spinal conditions. Methods:. This was a retrospective chart review of pediatric spine patients at a quaternary care hospital from October 2023 to September 2024. Inclusion criteria included any patients receiving a sCT for spinal evaluation. Patient demographics and imaging results were collected. For any patient with traditional CT (tCT) within 3 months of the sCT (n = 10), osseous anatomical measurements on the coronal, sagittal, and axial sequences were compared (10 total measurements per scan). Official radiology reads were also compared between sCT and tCT. Results:. Twenty-five patients underwent sCT of the spine (2 cervical and 23 lumbar). Indications included rule out congenital cervical anomalies in congenital muscular torticollis (2 patients), spondylolysis (13), spondylolisthesis (2), scoliosis/back pain (4), chronic back pain (4), and back pain with transitional lumbosacral anatomy (4). A total of 176 measurements of spinal osseous anatomy were performed. Comparing tCT with sCT, 62.5% of the measurements differed by less than 0.5 mm, 95.5% by less than 1 mm, and 4.5% differed by 1 mm or more. Conclusion:. sCT is a radiation-free alternative imaging modality for the evaluation of the osseous spine in children. sCT provides 3-dimensional imaging of the child’s bony anatomy, largely within 1 mm compared with a tCT. We believe sCT has significant clinical utility in the pediatric and adolescent population, allowing the diagnosis of both bony and soft tissue pathologies without exposing patients to radiation and using a single imaging study. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.